Clinical and genetic features of Chinese patients with lichen and macular primary localized cutaneous amyloidosis. (7th February 2019) - Lu, P.; Wu, F.‐F.; Rong, Z.‐L.; Fang, C.; Deng, C.‐C.; Bin, L.‐H.; Yang, B.
Summary: Background: Primary localized cutaneous amyloidosis (PLCA) is a chronic pruritic skin disorder. The genetic basis of familial (f)PLCA involves mutations in the oncostatin M receptor ( OSMR ) and interleukin‐31 receptor A ( IL31RA ) genes, but the disease pathophysiology is not fully understood. Aim: To investigate the OSMR mutation spectrum in patients with sporadic (s)PLCA/fPLCA, lichen/macular PLCA in mainland China. Methods: This study was carried out on 64 patients with sPLCA, along with 36 with fPLCA and 10 unaffected individuals collected from 23 unrelated Chinese families. Genomic DNA was extracted from peripheral blood samples. Mutation screening of 17 OSMR exons was performed by Sanger sequencing. Results: PLCA lesions are typically localized to the shins, forearm and back. Sequence analysis of OSMR exons demonstrated that the OSMR missense mutation rate in patients with fPLCA (63.89%) was significantly higher than that in patients with sPLCA (34.38%). The male/female ratio of patients carrying a homozygous OSMR mutation (0.29) was significantly lower than that of patients carrying a heterozygous OSMR mutation (1.08; P  < 0.05) and of patients with wildtype OSMR (1.75; P  < 0.01). Age of onset of PLCA with OSMR homozygous mutation (median age 20 years) was earlier than that of PLCA with OSMR heterozygous mutation (median age 32 years; P  < 0.01) or PLCA with wildtype genotype (median age 32 years; P  < 0.01). Conclusion: The present data indicate OSMR mutations as not only the main cause of fPLCA, but also the potential source of the pathogenesis of sPLCA, although the exact molecular mechanism remains unknown.